2015
DOI: 10.1166/jnn.2015.8372
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Plasma Treated Electrospun Polycaprolactone (PCL) Nanofiber Scaffold for Bone Tissue Engineering

Abstract: Polycaprolactone (PCL) nanofibers (PCL-NF) with uniform fibrous structure were fabricated by electrospinning. However, PCL-NF has hydrophobic surface, lacks functional groups and hence it is not a good substrate for cell adhesion. To improve the cell adhesion, PCL-NF surfaces were modified by low pressure RF discharge plasma treatment using monomer such as acrylic acid or oxygen gas. The plasma treated PCL-NFs improved the wettability and cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 1 publication
2
35
0
1
Order By: Relevance
“…This property, along with good compatibility and easy processing (melting point at 60°C), makes PCL an interesting substrate for tissue engineering (20)(21)(22)(23)(24)(25). However, like other synthetic polymers, PCL also lacks surface wettability and functional surface groups improving the cell attachment that are essential in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…This property, along with good compatibility and easy processing (melting point at 60°C), makes PCL an interesting substrate for tissue engineering (20)(21)(22)(23)(24)(25). However, like other synthetic polymers, PCL also lacks surface wettability and functional surface groups improving the cell attachment that are essential in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The observed reduction in PCL fiber diameters may be due to the etching effects of plasma treatment on polymers [39,40]. Recently, Ko et al reported a similar phenomenon in plasma-treated PCL fibers [39]. Supplementary Fig.…”
Section: Fiber Surface Morphology and Hydrophobicitymentioning
confidence: 96%
“…Compared to plasma-treated PCL and CSS fibers, however, the non-treated PCL fibers had large diameters, which would decrease the overall surface area available for protein immobilization. The observed reduction in PCL fiber diameters may be due to the etching effects of plasma treatment on polymers [39,40]. Recently, Ko et al reported a similar phenomenon in plasma-treated PCL fibers [39].…”
Section: Fiber Surface Morphology and Hydrophobicitymentioning
confidence: 99%
“…As the material for nanofiber formation, we used the synthetic polyester polycaprolactone known for its biodegradability within several months (Salgado et al 2012) and biocompatibility to hMSC (Valonen et al 2010;Ko et al 2015). The prepared nanofiber membrane from PCL had a basis weight of 36 g/m 2 , thickness of 200 µm and a fibre diameter of 110 ± 40 nm (Plate IX, Fig 1, and Fig 2).…”
Section: Preparation Of the Organic Carriermentioning
confidence: 99%